Como um Olhar de Pássaro? - Melo, Cristina Joanaz de; Arruda, Gilmar; Clare, Patricia (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
Looking at the past as a foreign country is perhaps an impossible challenge when we consider the cultural, subjective, identity burden present in the historian's work, or in general, in all human action, after all, this is a species that produces symbols and values, culture , who use them for all relationships between humans and other species. Perhaps only for an 'foreing-alien' would an ethnography of the relationships between humans and the natural world be possible. Through this metaphor, we seek to reach in the past examples of actions, practices and processes of preservation, restoration, care for the natural world, bringing them to the present to expand the space of experience, thus increasing the horizon of expectation in relation to the continuity of conditions of life on earth.